2018
DOI: 10.18805/ag.d-4711
|View full text |Cite
|
Sign up to set email alerts
|

Present status and diversity of avian fauna in Purbasthali bird sanctuary, West Bengal, India

Abstract: Birds play a crucial role in many food webs of aquatic ecosystem and the birds are known as good ‘bio-indicators’ as they are very sensitive to minor environmental changes. The present study was carried out in Purbasthali bird sanctuary of West Bengal (India) and its surroundings from January 2016 to December 2016 to explore the current status and diversity of avian fauna. The point count and line transect methods were implemented in bird counting. A total of 86 species of birds belonging to 31 families were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…). While our observations on the number of the bird species remain comparable to the Santragachi jheel, and other regions of West Bengal, the earlier observations from Purbasthali appear to be considerably higher (74 species reported by Mandal & Siddique 2018, 86 species reported byDebnath et al 2018), particularly because of the inclusion of several nonaquatic bird species. Similarly, in two other wetlands in Jalpaiguri, West Bengal, 42 and 80 species of birds were observed…”
supporting
confidence: 69%
See 1 more Smart Citation
“…). While our observations on the number of the bird species remain comparable to the Santragachi jheel, and other regions of West Bengal, the earlier observations from Purbasthali appear to be considerably higher (74 species reported by Mandal & Siddique 2018, 86 species reported byDebnath et al 2018), particularly because of the inclusion of several nonaquatic bird species. Similarly, in two other wetlands in Jalpaiguri, West Bengal, 42 and 80 species of birds were observed…”
supporting
confidence: 69%
“…The wetland of Purbasthali, physiographically an oxbow lake of Gangetic Alluvial Plains (Mandal & Siddique 2018), has long been familiar as it provides suitable habitat for a large number of bird species. However, few works have been accomplished (Jha 2013, Debnath et al 2018 on the diversity and distribution of various bird species that reside in this wetland. This is the first time when a survey was focused mainly on diversity of all kinds of waterbird considering their foraging guilds during midwinter, when they are known to show maximum abundance (Khan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Purbasthali wetland is an important repository of various resident and migratory water bird species as it provides favourable space for breeding, foraging, roosting and watering . Avifaunal diversity of Purbasthali wetland has been studied by Chowdhury (2017), , , Debnath et al (2018) and Chakraborty et al (2021). These works presented a checklist based on both water birds and terrestrial birds living around the wetland.…”
Section: Introductionmentioning
confidence: 99%
“…These works presented a checklist based on both water birds and terrestrial birds living around the wetland. Subsequently, 74 water bird species have been identified by however; Debnath et al (2018) found 86 species, Chowdhury (2017) reported 89 species while Chakraborty et al (2021) has identified 27 species. have emphasized how human intervention has reduced the diversity among waders.…”
Section: Introductionmentioning
confidence: 99%
“…The number of individuals residing in Mexico is unknown to date; however, approximately 50 nests have been documented in the wild and more than 60 specimens in captivity (CONABIO 2011). Birds play a crucial role in food webs of ecosystem and are known as 'bio-indicators' a sensitive to minor environmental changes (Debnath et al, 2018).…”
Section: Introductionmentioning
confidence: 99%